A STUDY ON INVESTOR’S LEVEL OF MINDFULNESS ABOUT COMMODITY MARKET - Ilankadhir, M.; Vijaya kumar, L. (International Journal of Psychosocial Rehabilitation, 2020)
The investigation entitled on financial specialist’s degree of mindfulness about item showcase. The administration of the Stock Broking Service is in a situation to know whether the speculators know about the ware showcase. To get the recommendation from the financial specialists for the further advancement in giving mindfulness program to the development of the association. The goals is to contemplate level of mindfulness, inclination, segment profile and the factors impacting the interest in commodity. Descriptrive investigate configuration is utilized in this examination. The self administrated survey was utilized to gather information from the respondents. The survey contained factor impacting the financial specialists in ware advertise. Utilizing a comfort examining approach, a sum of 160 clients were met at Stock Broking. Instruments utilized for investigation are rate examination, mean examination what’s more, weighted normal for dissecting essential information. The financial specialist level of instruction is among UG and PG. The age classification is between 25-30 and the sexual orientation is male. Larger part of the financial specialists know about the speculation in item advertise. The examination uncovers that singular financial specialists relies for the most part upon yearly salary and needs to procure exceptional yield in the present moment period. The inclination of venture is raw petroleum, silver, copper and gold contrasted with different products. The dominating elements affecting the interest in ware are Online programming, companions and financier.